2013
DOI: 10.3892/br.2013.138
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expression, different downstream processing of the disulfide-rich anti-tumor peptide Ranpirnase and its effect on the growth of human glioma cell line SHG-44

Abstract: Abstract. Ranpirnase (Onconase) is a frogspawn-derived disulfide-rich peptide with ribonuclease activity that may be used for tumor treatment. In the present study, we established an efficient approach for preparing mature ranpirnase which may be used for research and therapeutic purposes. The designed ranpirnase precursors carried a 6xHis-tag and were recombinantly expressed in Escherichia coli. After S-sulfonation, the precursors were purified by immobilized metal-ion affinity chromatography. Following remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…has indicated that Onconase may inhibit cell growth in the glioma SHG-44 cell line (26). In the present study, the results demonstrated that RC-RNase exerts antitumor activity on the human glioblastoma DBTRG, GBM8901 and GBM8401 cell lines.…”
Section: A B Csupporting
confidence: 56%
See 2 more Smart Citations
“…has indicated that Onconase may inhibit cell growth in the glioma SHG-44 cell line (26). In the present study, the results demonstrated that RC-RNase exerts antitumor activity on the human glioblastoma DBTRG, GBM8901 and GBM8401 cell lines.…”
Section: A B Csupporting
confidence: 56%
“…These results suggest that a number of the GBM8401 and GBM8901 cells may be resistant to RC-RNase. However, a previous study has revealed that Onconase can induce cytotoxic effects in the human glioma SHG-44 cell line (26), and the present study demonstrated that RC-RNase can exert cytotoxic effects on the human glioblastoma DBTRG, GBM8901 and GBM8401 cell lines. Overall, these studies suggest that frog ribonucleases exert potential antitumor effects on glioblastoma cells.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The recombinant CTX was prepared from a GST-6′His-CTX precursor by enzymatic cleavage and in vitro refolding, according to our previously described procedure ( 34 ). The recombinant Onc was prepared through heterologous expression of an N-terminally 6xHis-tagged Onc (6xHis-Onc) precursor by enzymatic cleavage, N-terminal cyclization and in vitro refolding, according to our previously described procedure ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…ONC specifically evades the interaction with the cytosolic ribonuclease inhibitor (RI) owing to its particular structure which lacks the RNase A key-loop residues involved in the interaction with RI [4][5][6]. Such a capacity confers to ONC a high cytotoxic activity against several human cancer cell types, such as glioma cells [7] or lymphoma B cells [8]. Notably, ONC is currently used in Phase II and Phase IIIb clinical trials as therapy against non-small cell lung cancer and against unresectable malignant mesothelioma, respectively [9].…”
Section: Introductionmentioning
confidence: 99%